The reflectivity in the S‐band and the broadband ultrasonic spectroscopy as new tools for the study of water relations in Vitis vinifera L. Issue 4 (7th December 2012) - Sancho‐Knapik, Domingo; Peguero‐Pina, José Javier; Medrano, Hipólito; Fariñas, María Dolores; Álvarez‐Arenas, Tomás Gómez; Gil‐Pelegrín, Eustaquio
Abstract : The large water requirements of Vitis vinifera L. together with an increase in temperature and drought events imply the need for irrigation in the driest areas of its distribution range. Generous watering may reduce grape quality so irrigation should be precisely regulated through the development of new methods of accurate irrigation scheduling based on plant 'stress sensing'. Two new methods, the reflectivity in the S‐band and the broadband ultrasonic spectroscopy, can be used as non‐invasive and reproducible techniques for the study of plant water relations in V. vinifera . On one hand, the measurement of reflectance at frequencies around 2.4 GHz gives an excellent accuracy when the changes in the existing area (S) between two reflectance curves are correlated with the relative water content (RWC). On the other hand, an improvement of the broadband ultrasonic spectroscopy based on the enlargement of the analysis frequency window provides, apart from the determination of the turgor loss point (TLP), additional information about the leaves without additional computational cost or additional leaf information requirements. Before TLP, the frequency associated with the maximum transmittance (f/fo ), the macroscopic elastic constant of the leaf in the Z direction (c33 ) and, specially, the variation of the attenuation coefficient with the frequency (n), were highly correlated with changes in RWC. Once turgor is lost, a shift in the parameters directly related to the attenuation of the signal was also observed. The use of both techniques allows for a more convincing knowledge of the water status in V. vinifera .